EXPLORING NEW TECHNOLOGY INTERVENTIONS IN NURSING FIELD. - Noura Hamoud Alqahtani, Nourh Yosef Abdullah Alabdulaziz, Amirah Sayah Sabih Alkuwaykibi, Abdulhadi Jafar Ali Alqahtani, Aeidha Aowed Jaber Alsulami, Haya Fahd Hamad Al Dosari, Manal Khalaf Al Duyayk, Mosaad Sayer Alruwaily, Munayfah Eid Alruwaili, Salma ,; Abdulmajeed Fahad Fayadh, Salma Hulel Raja Alotaibi, Ibrahim Dablan Aljaloud, Abdullah Ahmed Alghassab, Khalil Khareem Al-Shammary, Abdrabuh Saad Altamimi, Aqeel Mohamed Altamimi, (Chelonian Research Foundation, 2022)
Using technology to improve precision health, the National Institute of Nursing Research (NINR) Research Centers are leading the way. They specialize in defining biomarkers, delivering customized therapies for a range of health issues, and characterizing symptom profiles. Technology is more effective as a tool in nursing science when it is used within a framework that is focused on the needs of the user. Establishing precise theoretical connections between interventions and technology use, in addition to open practices in user-centered design, testing, and evaluation, are essential to this attempt. To stop health disparities from growing, it is essential to incorporate best practices for involving minority and underprivileged groups. Even if the use of technology for self- and symptom management has grown significantly, it is still crucial to provide accurate and consistent data to enable its application in clinical settings. Adopting the multistep, standardized process described in this article for technology creation and testing is relevant to nursing research worldwide.This roadmap can be used by interdisciplinary teams in conjunction with nurse scientists to develop new technologies or implement those that already exist. Ultimately, the goals of precision health and nursing science are aligned when it comes to supporting each other and providing tailored therapies that improve health and well-being. Technology has the potential to completely transform healthcare delivery and meet the vast range of demands of people on the planet, thanks to the cooperative efforts of NINR Research Centers and the application of reliable methodology. Key Words: Nursing, Technology, Innovations, National Institute of Nursing Research.